Tuning of structure, grain orientation and mechanical properties in reactively sputtered (Al, Mo, Ta, V, W)N. (January 2022) - Kretschmer, Andreas; Wojcik, Tomasz; Schuster, Roman; Yalamanchili, Kumar; Rudigier, Helmut; Mayrhofer, Paul Heinz
Graphical abstract: Highlights: (Al, Mo, Ta, V, W)N0.79 and -N0.33 show columnar microstructures. The oxynitride features a renucleated finer, randomly oriented microstructure. N-deficiency of (Al, Mo, Ta, V, W)N is beneficial for hardness and phase stability. The oxynitride is harder than the N-rich nitride in as-deposited state. The oxynitride cracks open during annealing due to formation of binary oxides. Abstract: (Al, Mo, Ta, V, W)-N0.79, -N0.33, and -N0.88 O0.12 coatings were sputtered in N2 -rich, N2 -lean, and N2 +O2 containing atmospheres. The face-centered cubic structured coatings feature as-deposited hardness values of 32.3, 39.7, and 34.5 GPa, respectively. The (Al, Mo, Ta, V, W) N0.79 and (Al, Mo, Ta, V, W)N0.33 consist of highly oriented columns, plus some very large grains in the latter coating. During vacuum annealing at 800 °C for 30 h, the (Al, Mo, Ta, V, W)N0.79 loses N down to 25 at.%, while the (Al, Mo, Ta, V, W)N0.33 remains stable. Their alignment in chemical composition also caused an approach of their hardness values with 35.2 and 38.1 GPa, respectively. The (Al, Mo, Ta, V, W)N0.88 O0.12 exhibits partly tilted and randomly oriented smaller columnar grains than the nitrides, and the hardness drops from 34.5 to only 14.1GPa when vacuum annealed due to massive phase-transformations toward individual oxides and the connected crack formation.